Sediment Remediation by Microbial Fuel Cells and Effect of Vertical Position of Anode Buried in Sediment - MAKI, Hideaki; KUSUNOKI, Kazuya; WATANABE, Tomohide; SYUTSUBO, Kazuaki; KUBOTA, Keiichi (Journal of Japan Society on Water Environment, 2017)
In the present study, sediment microbial fuel cells (SMFCs) were applied for the amendment of a marine sediment core sample from Tokyo Bay to evaluate their efficacy for bioremediation and the effect of the depth of the anode in the sediment. SMFCs were operated for 55 days, and the maximum power density reached 8.5 mW m-2. The sediment oxidoreduction potential (ORP) continuously increased from -197 mV to -17 mV during the SMFC operation, and the oxygen consumption rate of the sediment was reduced by 15％. The reduction in the oxygen consumption rate was observed from 16 to 32 days after SMFC installation, during which an increase in the current density of the SMFC was observed. The anode depth had a significant effect on the power generation performance of the SMFC. In particular, an SMFC using an anode placed at the surface of the sediment exhibited a very low power density of 3.0 mA m-2 compared with an anode placed deep in the sediment (16.5 mA m-2) . To promote the bioremediation of sediment, the anode must be set at the surface of the sediment as well as in a deeper layer.